Model Komunikasi Antarbudaya dalam mewujudkan Nilai-nilai Multikulturalisme melalui Kearifan Lokal Marjambar di Kelurahan Bunga Bondar Sipirok - Rezki Aulia; Rahmanita Ginting; Leylia Khairani (CERED Indonesia, 2020)
This study aims to analyze the intercultural communication model and the values of multiculturalism contained in the local wisdom of marjambar. Marjambar is a form of local wisdom in the Bunga Bondar sub-district which is carried out by the local community without any command from various parties, in its implementation, marjambar is carried out by distributing cookies typical of the local community during religious holidays, namely just before Hari Raya Eid al-Fitr performed by Muslims and one day before the New Year by Christians. To obtain the data used a qualitative descriptive research method, then in the data collection technique was done by interview, observation and documentation. The results of data collection show that the intercultural communication model occurs between communities of different ethnicities and religions. In realizing the values of multiculturalism, the community inherits a philosophy of life,